Polymer electrolyte membrane and solid polymer fuel cell
A polymer electrolyte membrane with an ionic compound containing sulfur atoms and a reinforcing material addresses durability and conductivity issues in fuel cells, ensuring long-term stability and performance.
Patent Information
- Application Number
- JP2020118658
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-09
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-07-09
AI Technical Summary
Conventional polymer electrolyte fuel cells face issues with chemical durability and power generation characteristics under high temperature and low humidity conditions, leading to pinhole formation and cross leaks, and the addition of Ce or Ce compounds to improve durability results in decreased proton conductivity over time.
Incorporation of a polymer electrolyte membrane containing a predetermined amount of an ionic compound with sulfur atoms, along with a reinforcing material, to enhance chemical durability without affecting power generation characteristics.
The polymer electrolyte membrane maintains excellent chemical durability and power generation characteristics by stabilizing the ionic compound within the fuel cell, preventing deterioration and maintaining proton conductivity.
Smart Images

Figure 0007607414000012 
Figure 0007607414000013 
Figure 0007607414000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymer electrolyte membrane and a solid polymer fuel cell. [Background technology]
[0002] A fuel cell obtains electrical energy through an electrochemical reaction between a fuel (hydrogen source) and an oxidant (oxygen) inside a cell. In other words, the chemical energy of the fuel is directly converted into electrical energy. Fuel sources that can be used include pure hydrogen, petroleum that contains hydrogen, natural gas (methane, etc.), and methanol. Fuel cells themselves have the advantage that they generate little noise because they have no mechanical parts, and in principle can generate electricity semi-permanently by continuously supplying fuel and oxidant from the outside. The electrolyte of a fuel cell is classified as a liquid electrolyte or a solid electrolyte, and among these, a fuel cell that uses a polymer electrolyte membrane as the electrolyte is called a polymer electrolyte fuel cell. In particular, polymer electrolyte fuel cells can operate at lower temperatures than other types of fuel cells, and are therefore expected to be used as an alternative power source for automobiles, home cogeneration systems, and portable generators.
[0003] A polymer electrolyte fuel cell includes a membrane electrode assembly (MEA) in which gas diffusion electrodes, each of which is a stack of an electrode catalyst layer and a gas diffusion layer, are bonded to both sides of a proton exchange resin membrane. The proton exchange resin membrane referred to here is a material that has a strong acidic group, such as a sulfonic acid group or a carboxylic acid group, in the polymer chain and has the property of selectively transmitting protons. As such a proton exchange resin membrane, a perfluoro-based proton exchange resin membrane, such as Nafion (registered trademark, manufactured by DuPont, USA), which has high chemical stability, is preferably used.
[0004] A fuel cell operates by supplying a fuel (e.g., hydrogen) to the gas diffusion layer on the anode side and an oxidant (e.g., oxygen or air) to the gas diffusion layer on the cathode side, and connecting both electrodes with an external circuit. Specifically, when hydrogen is used as fuel, hydrogen is oxidized on the anode catalyst to generate protons, which pass through the proton-conductive polymer in the anode catalyst layer, move through the proton exchange resin membrane, and reach the cathode catalyst layer through the proton-conductive polymer in the cathode catalyst layer. Meanwhile, electrons generated simultaneously with the protons by the oxidation of hydrogen pass through the external circuit to reach the cathode gas diffusion layer, where they react with the protons and oxygen in the oxidant on the cathode catalyst to generate water, at which time electrical energy can be extracted. In this case, the proton exchange resin membrane must also function as a gas barrier. If the proton exchange resin has high gas permeability, hydrogen on the anode side will leak to the cathode side and oxygen on the cathode side will leak to the anode side, i.e., cross leakage will occur, resulting in a chemical short circuit and making it impossible to obtain a satisfactory voltage.
[0005] Such solid polymer fuel cells are usually operated at about 80°C to obtain high output characteristics. However, when used in automobiles, it is desirable to be able to operate the fuel cell under high temperature and low humidity conditions, assuming that the vehicle will be driven in the summer. However, when a fuel cell is operated for a long time under high temperature and low humidity conditions using a conventional perfluoro-based proton exchange resin, there is a problem that pinholes are formed in the proton exchange resin, causing cross leakage, and sufficient durability cannot be obtained.
[0006] To address this issue, methods have been used to reinforce the electrolyte membrane by combining it with a nanofiber-like porous material (see, for example, Patent Documents 1 to 3). These methods are said to improve the mechanical strength of the membrane, making it physically less likely to develop pinholes. In addition, compared to conventional perfluoroproton exchange resin membranes, they are said to be less likely to develop pinholes due to a reduction in the dry-wet dimensional change that occurs when the membrane swells in a wet state and shrinks in a dry state.
[0007] In addition, in a polymer electrolyte fuel cell, peroxides are generated in the catalyst layer formed between the polymer electrolyte membrane and the electrode interface by the cell reaction. The generated peroxides become peroxide radicals and react with the polymers constituting the electrolyte membrane, causing deterioration of the electrolyte membrane.
[0008] To address this issue, a method is known in which Ce (cerium) or a Ce compound is added to the electrolyte membrane or MEA to improve chemical durability (see, for example, Patent Documents 4 to 6). It is believed that adding Ce or a Ce compound to the electrolyte membrane used in a polymer electrolyte fuel cell suppresses the generation of peroxide radicals in the cell and captures the generated peroxide radicals. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 4895563 [Patent Document 2] Patent No. 5798186 [Patent Document 3] JP 2016-58152 A [Patent Document 4] Patent No. 4972867 [Patent Document 5] Patent No. 4810868 [Patent Document 6] Patent No. 5331122 Summary of the Invention [Problem to be solved by the invention]
[0010] As described above, it is said that the chemical durability of the electrolyte membrane can be improved by adding Ce or Ce compounds to the electrolyte membrane. However, since the Ce or Ce compounds added to the electrolyte membrane exist in the electrolyte membrane in the form of ions, they are mobilized by the water generated by the cell reaction. Therefore, when a fuel cell equipped with the electrolyte membrane is operated for a long time, the Ce ions bond with the proton-conducting polymer (ionomer) in the catalyst layer, which reduces the proton conductivity and thus reduces the power generation characteristics, which is a problem.
[0011] Therefore, an object of the present invention is to provide a polymer electrolyte membrane that is excellent in chemical durability while maintaining power generation characteristics. [Means for solving the problem]
[0012] As a result of intensive research into the above-mentioned problems, the inventors have found that a polymer electrolyte membrane containing a predetermined amount of an ionic compound containing a sulfur atom is a membrane having excellent chemical durability without deteriorating the power generation characteristics, and have thus completed the present invention.
[0013] That is, the present invention includes the following aspects. [1] A polymer electrolyte membrane containing an ionic compound containing a sulfur atom, A polymer electrolyte membrane, wherein the content of the ionic compound containing a sulfur atom is 0.10 ppm or more and 100 ppm or less, expressed as parts by mass per part by mass of the polymer electrolyte membrane. [2] The molecular weight of the ionic compound containing a sulfur atom is 300 g / mol or less. [1] The polymer electrolyte membrane according to claim 1. [3] The sulfur atom-containing ionic compound is represented by formula (1): The polymer electrolyte membrane according to [1] or [2]. [ka] (In the formula, R represents a monovalent organic group having 1 to 10 carbon atoms, hydrogen, or a hydroxyl group.) [4] Further comprising one or more reinforcing materials in the form of particles, fiber sheets, and nonwoven fabrics; The polymer electrolyte membrane according to any one of [1] to [3]. [5] The reinforcing material contains at least one polymer selected from polyethersulfone, polyphenylene sulfide, and polysulfone. [4] The polymer electrolyte membrane according to claim 1. [6] The proportion of the reinforcing material is 1 to 20 mass% based on the total amount of the polymer electrolyte membrane. The polymer electrolyte membrane according to [4] or [5]. [7] A solid polymer fuel cell comprising the polymer electrolyte membrane according to any one of [1] to [6]. Effect of the Invention
[0014] According to the present invention, it is possible to provide a polymer electrolyte membrane having excellent chemical durability without deteriorating the power generation characteristics. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a schematic diagram for explaining an embodiment of a composite using the nanofiber sheet and nonwoven fabric according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram for explaining an aspect of composite using particles according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as the present embodiment) will be described in detail with reference to the drawings as necessary, but the present invention is not limited to the present embodiment. The present invention can be modified in various ways without departing from the gist of the invention.
[0017] The polymer electrolyte membrane of the present embodiment (hereinafter also simply referred to as "electrolyte membrane") contains an ionic compound containing a sulfur atom. In the polymer electrolyte membrane of the present embodiment, the content of the ionic compound containing a sulfur atom is 0.10 ppm or more and 100 ppm or less in parts by mass relative to 1 part by mass of the polymer electrolyte membrane.
[0018] The polymer electrolyte membrane of the present embodiment has high durability against chemical deterioration of the electrolyte membrane components caused by peroxides and radicals, even without the addition of inorganic compounds or the like for improving chemical durability. In addition, the addition of inorganic compounds to the electrolyte membrane can be suppressed, and deterioration of power generation characteristics due to uneven distribution of additives inside the fuel cell during long-term operation can be prevented. In addition, ionic compounds containing sulfur atoms undergo an equilibrium reaction in the water generated by the cell reaction contained in the electrolyte membrane, and therefore exist in a stable state in the reaction system, unlike Ce or Ce compounds. Therefore, even if a fuel cell equipped with the electrolyte membrane is operated for a long period of time, the ionic compounds do not flow like Ce ions and bond with the proton-conducting polymer (ionomer) in the catalyst layer, and therefore do not decrease the proton conductivity or the power generation characteristics.
[0019] <Polymer electrolyte> As the polymer electrolyte that can be used in this embodiment, a perfluorocarbon polymer compound having an ion exchange group is preferable from the viewpoint of chemical stability.
[0020] The ion exchange group is not particularly limited, but examples thereof include a sulfonic acid group, a sulfonimide group, a sulfonamide group, a carboxylic acid group, and a phosphoric acid group. Among these, a sulfonic acid group is preferable. The ion exchange group may be used alone or in combination of two or more kinds.
[0021] The perfluorocarbon polymer compound is not particularly limited, but more specifically, a polymer represented by the following formula [1] can be mentioned. -[CF2CX 1 X 2 ] a-[CF2-CF(-O-(CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 4 )] g - [1] Here, in the formula, X 1 , X 2 and X 3 each independently represents a halogen atom, a perfluoroalkyl group having 1 to 3 carbon atoms, or a fluorochloroalkyl group. X 4 represents COOZ, SO3Z, PO3Z2, or PO3HZ. Here, Z represents a hydrogen atom, an alkali metal atom, an alkaline earth metal atom, or amines (NH4, NH3R 3 , NH2R 3 R 4 , NHR 3 R 4 R 5 , or NR 3 R 4 R 5 R 6 ). Also, R 3 , R 4 , R 5 and R 6 each independently represents an alkyl group or an arene group.
[0022] Among these, perfluorocarbon sulfonic acid resins represented by the following formula [2] or [3] or their metal salts are preferable. -[CF2CF2] a -[CF2-CF(-O-(CF2-CF(CF3)) b -O-(CF2) c -SO3X)] d - [2] Here, in the formula, a and d satisfy 0 ≦ a < 1, 0 < d ≦ 1, and a + d = 1. b is an integer of 1 or more and 8 or less. c is an integer of 0 or more and 10 or less. X represents a hydrogen atom or an alkali metal atom. ―[CF2CF2] e-[CF2-CF(-O-(CF2) f -SO3Y)] g - [3] Here, in the formula, e and g satisfy 0 ≦ e < 1, 0 < g ≦ 1, and e + g = 1. f is an integer from 0 to 10. Y represents a hydrogen atom or an alkali metal atom.
[0023] The perfluorocarbon polymer compound having an ion-exchange group that can be used in this embodiment is not particularly limited. For example, it can be produced by polymerizing a precursor polymer represented by the following formula [4] and then performing alkali hydrolysis, acid treatment, etc. -[CF2CX 1 X 2 a -[CF2-CF(-O-(CF2-CF(CF2X 3 )) b -O c -(CFR 1 ) d -(CFR 2 ) e -(CF2) f -X 5 )] g - [4] Here, in the formula, X 1 , X 2 and X 3 each independently represent a halogen atom or a perfluoroalkyl group having 1 to 3 carbon atoms. a and g satisfy 0 ≦ a < 1, 0 < g ≦ 1, and a + g = 1. b is an integer from 0 to 8. c is 0 or 1. d and e are independently integers from 0 to 6. f is an integer from 0 to 10. However, d + e + f is not equal to 0. R 1 and R 2 each independently represent a halogen atom, a perfluoroalkyl group having 1 to 10 carbon atoms, or a fluorochloroalkyl group. X 5 is COOR 7 , COR 8 or SO2R 8 . Here, R 7 represents an alkyl group having 1 to 3 carbon atoms. R 8 represents a halogen atom.
[0024] The precursor polymer is not particularly limited, but can be produced, for example, by copolymerizing a fluorinated olefin compound and a fluorinated vinyl compound.
[0025] Here, the fluorinated olefin compound is not particularly limited, but examples thereof include compounds represented by the following formula [5]. CF2=CFZ [5] In the formula, Z represents a hydrogen atom, a chlorine atom, a fluorine atom, a perfluoroalkyl group having 1 to 3 carbon atoms, or a cyclic perfluoroalkyl group which may contain oxygen.
[0026] The vinyl fluoride compound is not particularly limited, but examples thereof include the compounds shown below. CF2=CFO(CF2)2-SO2F, CF2=CFOCF2CF(CF3)O(CF2)2-SO2F, CF2=CF(CF2)2-SO2F, CF2=CF(OCF2CF(CF3)) z -(CF2) z -SO2F, CF2 = CFO(CF2) z -CO2R, CF2 = CFOCF2CF(CF3)O(CF2) z -CO2R, CF2=CF(CF2) z -CO2R, CF2=CF(OCF2CF(CF3)) z -(CF2)2-CO2R In the formula, Z is an integer of 1 to 8, and R is an alkyl group having 1 to 3 carbon atoms.
[0027] The precursor polymer as described above can be synthesized by known means. The synthesis method is not particularly limited, but the following methods can be mentioned. (i) A method (solution polymerization) in which a vinyl fluoride compound and a fluorinated olefin gas are reacted with each other in a state of being filled and dissolved in a polymerization solvent such as a fluorinated hydrocarbon to carry out polymerization. As the fluorinated hydrocarbon, for example, a group of compounds collectively known as "fluorocarbons", such as trichlorotrifluoroethane and 1,1,1,2,3,4,4,5,5,5-decafluoropentane, can be suitably used. (ii) A method in which the polymerization of a vinyl fluoride compound is carried out using the vinyl fluoride compound itself as a polymerization solvent without using a solvent such as a fluorinated hydrocarbon (bulk polymerization). (iii) A method in which an aqueous solution of a surfactant is used as a polymerization solvent, and a vinyl fluoride compound and a fluorinated olefin gas are reacted with each other while the compound is filled and dissolved in the polymerization solvent to carry out polymerization (emulsion polymerization). (iv) A method in which an aqueous solution of a surfactant and an emulsifier such as alcohol is used, and a vinyl fluoride compound and a fluorinated olefin gas are reacted with each other in an emulsified state in the aqueous solution to polymerize the vinyl fluoride compound (miniemulsion polymerization, microemulsion polymerization). (v) A method in which an aqueous solution of a suspension stabilizer is used, and a vinyl fluoride compound is reacted with a fluorinated olefin gas while the compound is suspended in the aqueous solution to carry out polymerization (suspension polymerization).
[0028] The polymer electrolyte membrane of this embodiment preferably further contains a reinforcing material. Examples of the reinforcing material in this embodiment include polyolefin resins (e.g., polyethylene, polypropylene, and polymethylpentene), styrene resins (e.g., polystyrene), polyester resins (e.g., polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polycarbonate, polyarylate, and wholly aromatic polyester resins), acrylic resins (e.g., polyacrylonitrile, polymethacrylic acid, polyacrylic acid, and polymethyl methacrylate), polyamide resins (e.g., nylon 6, nylon 66, and aromatic polyamide resins), polyether resins (e.g., polyether ketone, polyacetal, polyphenylene), and the like. ether, modified polyphenylene ether and aromatic polyether ketone), urethane-based resin, chlorine-based resin (e.g. polyvinyl chloride and polyvinylidene chloride), fluorine-based resin (e.g. polytetrafluoroethylene and polyvinylidene fluoride (PVDF)), polyphenylene sulfide (PPS), polyamide-imide-based resin, polyimide-based resin (PI) polyetherimide-based resin, aromatic polyetheramide-based resin, polysulfone-based resin (e.g. polysulfone (PSU) and polyethersulfone (PES)), polyazole-based resin (e.g. polybenzimidazole (PBI), polybenzoxazole, polybenzothiazole and polypyrrole), cellulose-based resin, and polyvinyl alcohol-based resin. These may be used alone or in combination of two or more. From the viewpoint of producing a sulfur compound that contains sulfur atoms and is thought to act as a radical scavenger, polyphenylene sulfide (PPS), polysulfone-based resins (e.g., polysulfone (PSU) and polyethersulfone (PES)), and polybenzothiazole are preferred, and from the viewpoint of moldability, it is more preferred to contain, as a main component, one or more polymers selected from the group consisting of polyphenylene sulfide (PPS), polysulfone (PSU), and polyethersulfone (PES), which are represented by formulas [I] to [III].Here, "main component" means that one or more selected from the group consisting of polyphenylene sulfide (PPS), polysulfone (PSU), and polyethersulfone (PES) is usually 80% or more, preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more of the total amount of the reinforcing material. By being 80% or more of the total amount of the reinforcing material, it is possible to reliably exert the effect, by being 90% or more, it is possible to shorten the time of heat treatment (annealing treatment described later) for exerting the effect, by being 95% or more, it is possible to suppress the influence of other components, and by being 98% or more, it is possible to suppress the fluctuation range of the content of sulfur compounds caused by heat treatment (annealing treatment) to a range of 5 ppm. Reinforcing materials containing these polymers have even better chemical resistance and heat resistance, and are more stable when combined with a fluoropolymer electrolyte membrane.
[0029] [ka]
[0030] [ka]
[0031] [ka]
[0032] Specific examples of the form of the reinforcing material contained in the polymer electrolyte membrane of the present embodiment include particles, a fiber sheet, and a nonwoven fabric. From the viewpoint of improving durability, it is preferable to contain a reinforcing material in one or more forms selected from these.
[0033] The form of the particulate reinforcing material is not particularly limited, but from the viewpoint of improving dispersibility to realize a reinforcing effect throughout the electrolyte membrane, it is preferable that the average particle size is 0.1 to 20 μm. By making the particle size 0.1 μm or more, the effect of improving chemical durability can be realized, and by making it 20 μm or less, dispersibility within the polymer electrolyte membrane can be ensured.
[0034] The form of the reinforcing material, such as a fiber sheet or nonwoven fabric, is not particularly limited, but from the viewpoint of preventing an increase in resistance due to compounding, the fiber diameter is preferably 200 to 600 nm, and more preferably 300 to 500 nm. By making the fiber diameter 200 nm or more, the effect of the reinforcing material can be exhibited, by making it 300 nm or more, the effect of improving chemical durability can be exhibited, by making it 600 nm or less, compounding with the polymer electrolyte can be facilitated, and by making it 500 nm or less, an increase in the resistance of the polymer electrolyte membrane when compounded can be suppressed.
[0035] The method for producing the fiber sheet reinforcing material is not particularly limited, but may be, for example, an electrospinning method. The method for producing the nonwoven fabric reinforcing material is not particularly limited, but may be, for example, a melt-blowing method.
[0036] The polymer electrolyte membrane formed by compounding the reinforcing material and the polymer electrolyte as described above generates an ionic compound containing a sulfur atom that captures peroxides and peroxide radicals in the heat treatment (annealing) process during membrane formation described below. It is believed that this ionic compound containing a sulfur atom captures peroxides and peroxide radicals, suppresses chemical deterioration of the electrolyte membrane components caused by the peroxides and peroxide radicals, and improves the chemical durability of the electrolyte membrane.
[0037] The proportion of the reinforcing material is preferably 1 to 20 mass % relative to the total amount of the polymer electrolyte membrane, more preferably 5 to 20 mass %, and even more preferably 7 to 20 mass %. By setting the proportion of the reinforcing material to 1 to 20 mass %, it becomes easy to form a composite with the polymer electrolyte, by setting it to 5 to 20 mass %, it is possible to exert the effect as a reinforcing material, and by setting it to 7 to 20 mass %, it is possible to adjust the content of the ionic compound containing a sulfur atom in the polymer electrolyte membrane to 0.10 ppm or more and 100 ppm or less.
[0038] <Heat treatment (annealing treatment)> The annealing step is carried out to enhance and stabilize the mechanical strength of the produced electrolyte membrane itself, as described later in the process for producing a polymer electrolyte membrane. Annealing is sometimes performed at temperatures above the glass transition temperature of the polymer electrolyte (for example, 170°C or higher in the case of perfluorocarbon sulfonic acid resin) to increase mechanical strength. On the other hand, PPS, PSU, PES, and the like used as reinforcing materials may decompose when annealed at 170°C or higher, generating ionic compounds containing sulfur atoms. It was thought that these ionic compounds containing sulfur atoms would poison the catalyst, thereby reducing the power generation characteristics of the polymer electrolyte membrane. However, as a result of examining the polymer electrolyte membrane, it was newly found that the polymer electrolyte membrane annealed at 170° C. or higher has high chemical durability. This is believed to be because sulfur compounds generated by decomposition of the reinforcing material during the annealing process poison the catalyst while capturing peroxides and peroxide radicals generated in the operating battery. As a result, the amount of peroxides and peroxide radicals reacting with the electrolyte membrane is reduced, and chemical durability is improved. The polymer electrolyte membrane of the present embodiment contains a predetermined amount of an ionic compound containing a sulfur atom, thereby improving chemical durability while maintaining power generation characteristics.
[0039] The heat treatment is carried out, for example, in the process of forming a polymer electrolyte membrane. The heat treatment method is not particularly limited, but examples thereof include indirect heating methods using hot air, infrared rays, and microwaves. The indirect heating mentioned here refers to a method of heating by applying a heat source from the outside, rather than the polymer electrolyte membrane itself generating heat. For example, heating by hot air is a method of heating the entire polymer electrolyte membrane by blowing hot air against the polymer electrolyte membrane, and performing an annealing treatment. Heating by infrared rays or microwaves is a method of vibrating molecules by irradiating them with electromagnetic waves of a specific wavelength, generating vibrational heat. In particular, in the polymer electrolyte membrane, ion exchange groups form clusters, and water is bound inside the clusters. By irradiating electromagnetic waves of a wavelength at which the bound water vibrates, vibrational heat is generated and an annealing treatment is performed. This makes it possible to generate a heat amount equivalent to 170°C or more without increasing the temperature of the coating surface, so that the thermal decomposition of the reinforcing material can be minimized. In other words, the amount of sulfur compounds generated can be suppressed to 100 ppm or less, and only chemical durability can be improved without reducing the power generation characteristics. In this way, by controlling the temperature of the electrolyte membrane during the annealing treatment, the amount of thermal decomposition of the reinforcing material can be controlled, and the content of ionic compounds containing sulfur atoms can also be controlled.
[0040] The content of the ionic compound containing sulfur atoms in the polymer electrolyte membrane of this embodiment is 0.10 ppm or more and 100 ppm or less, preferably 1 ppm or more and 50 ppm or less, more preferably 5 ppm or more and 30 ppm or less, in terms of parts by mass relative to 1 part by mass of the polymer electrolyte membrane. By making the content of the ionic compound containing sulfur atoms 0.10 ppm or more, it is possible to exhibit the effect of improving chemical durability, by making it 1 ppm or more, it is possible to uniformly disperse the ionic compound in the planar direction of the polymer electrolyte membrane, by making it 5 ppm or more, it is possible to uniformly exhibit the effect of improving chemical durability in the polymer electrolyte membrane, by making it 100 ppm or less, it is possible to suppress the decrease in power generation toxicity due to catalyst poisoning, by making it 50 ppm or less, it is possible to suppress the decrease in power generation characteristics due to catalyst poisoning to a small amount, and by making it 30 ppm or less, it is possible to exhibit power generation characteristics equivalent to those of a polymer electrolyte membrane without catalyst poisoning. The method for controlling the content to within the range of 0.10 ppm or more and 100 ppm or less is not particularly limited, and examples thereof include a method in which a reinforcing material such as PPS, PSU, or PES is blended with the polymer electrolyte membrane, and the polymer electrolyte membrane is subjected to a heat treatment during production.
[0041] <Ionic compounds containing sulfur atoms> In this embodiment, the ionic compound containing a sulfur atom is a compound that generates sulfate ions, hydrogen sulfate ions, or sulfite ions. The molecular weight of the ionic compound containing a sulfur atom in this embodiment is preferably 300 g / mol or less. If it is 300 g / mol or less, it can be uniformly dispersed in the polymer electrolyte membrane. The lower limit of the molecular weight is not particularly limited, but it is usually 30 g / mol or more.
[0042] The ionic compound containing a sulfur atom in the present embodiment is not particularly limited, but is preferably a compound represented by formula (1). A compound having a structure such as formula (1) can be easily ionized and can be stably present in the polymer electrolyte membrane.
[0043] [ka]
[0044] In the formula, R represents a monovalent organic group having 1 to 10 carbon atoms, hydrogen, or a hydroxyl group.
[0045] The ionic compound containing a sulfur atom is not particularly limited, but examples thereof include sulfuric acid which generates sulfate ions and hydrogen sulfate ions, and sulfurous acid which generates sulfite ions.
[0046] These identifications can be performed using IC-MS. The polymer electrolyte membrane is immersed in ethanol to extract the decomposed ionic compounds, and the structures of the ionic compounds containing sulfur atoms are determined using IC-MS.
[0047] From the viewpoint of increasing the accuracy of the quantification of the ionic compound containing a sulfur atom contained in the polymer electrolyte membrane, it is preferable to determine the content of the ionic compound containing a sulfur atom by quantifying the compounds corresponding to the ionic compound containing a sulfur atom in the polymer electrolyte membrane (compounds generated simultaneously upon decomposition by heat treatment), for example, the compounds represented by formulas [IV], [V] and [VI]. Specifically, for example, it is preferable to determine the content of the ionic compound containing a sulfur atom by immersing the polymer electrolyte membrane in ethanol to extract the compounds represented by formulas [IV], [V] and [VI] generated simultaneously upon decomposition, and quantifying them by GC / MS.
[0048] [ka]
[0049] [ka]
[0050] [ka]
[0051] <Method of manufacturing polymer electrolyte membrane> A method for producing the polymer electrolyte membrane of this embodiment will be described. The polymer electrolyte membrane of this embodiment is preferably produced as a composite electrolyte membrane by combining a fluorine-based polymer electrolyte membrane with a reinforcing material in one or more forms selected from particles, a fiber sheet, and a nonwoven fabric. For example, the polymer electrolyte membrane can be obtained by filling the voids in a nanofiber sheet with the fluorine-based polymer electrolyte membrane.
[0052] The fluoropolymer electrolyte solution that can be used when producing the electrolyte membrane according to the present embodiment contains the above-mentioned fluoropolymer electrolyte solution and, if necessary, other additives. This fluoropolymer electrolyte solution is used for the composite with the nanofiber sheet as is or after a process such as filtration or concentration. Alternatively, this solution can be used alone or mixed with other electrolyte solutions.
[0053] Next, the method for producing the fluoropolymer electrolyte solution will be described in more detail. The method for producing the fluoropolymer electrolyte solution is not particularly limited, and for example, after obtaining a solution in which the fluoropolymer electrolyte is dissolved or dispersed in a solvent, an additive is dispersed in the liquid as necessary. Alternatively, the fluoropolymer electrolyte is first melt-extruded, and then mixed with the additive through a process such as stretching, and the mixture is dissolved or dispersed in a solvent. In this way, a fluoropolymer electrolyte solution is obtained.
[0054] More specifically, first, a molded product made of a precursor polymer of a fluorine-based polymer electrolyte is immersed in a basic reaction liquid and hydrolyzed. This hydrolysis treatment converts the precursor polymer of the fluorine-based polymer electrolyte into a fluorine-based polymer electrolyte. Next, the hydrolyzed molded product is thoroughly washed with warm water or the like, and then the molded product is subjected to an acid treatment. The acid used in the acid treatment is not particularly limited, but mineral acids such as hydrochloric acid, sulfuric acid, and nitric acid, and organic acids such as oxalic acid, acetic acid, formic acid, and trifluoroacetic acid are preferred. This acid treatment protonates the precursor polymer of the fluorine-based polymer electrolyte, and a fluorine-based polymer electrolyte, for example, a perfluorocarbon sulfonic acid resin, is obtained.
[0055] The above-mentioned molded article (molded article containing a fluorine-based polymer electrolyte) treated with an acid as described above is dissolved or suspended in a solvent capable of dissolving or suspending the above-mentioned fluorine-based polymer electrolyte (solvent having good affinity with the polymer). Examples of such a solvent include water, protic organic solvents such as ethanol, methanol, n-propanol, isopropyl alcohol, butanol, and glycerin, and aprotic organic solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. These are used alone or in combination of two or more. In particular, when one type of solvent is used, it is preferable that the solvent is water. By using water as a solvent, the conduction of protons is facilitated. In addition, when two or more types are used in combination, a mixed solvent of water and a protic organic solvent is preferable. If the mixed solvent is water and a protic organic solvent, it is easy to dissolve or suspend the polymer electrolyte.
[0056] The method of dissolving or dispersing (suspending) the fluorine-based polymer electrolyte in the solvent is not particularly limited. For example, the fluorine-based polymer electrolyte may be dissolved or dispersed in the above-mentioned solvent as it is. However, it is preferable to dissolve or disperse the fluorine-based polymer electrolyte in the solvent at a temperature range of 0 to 250°C under atmospheric pressure or sealed conditions such as an autoclave. In particular, when water and a protic organic solvent are used as the solvent, the mixing ratio of water and the protic organic solvent can be appropriately selected depending on the dissolving method, dissolving conditions, type of fluorine-based polymer electrolyte, total solid concentration, dissolving temperature, stirring speed, etc. However, the mass ratio of the protic organic solvent to water is preferably 0.1 to 10 protic organic solvent to water, more preferably 0.1 to 5 protic organic solvent to water. If the protic organic solvent is 0.1 to 10 protic organic solvent to water, the polymer electrolyte can be easily dissolved or dispersed, and if the protic organic solvent is 0.1 to 5 protic organic solvent to water, the solvent can be easily removed during the manufacturing process.
[0057] The fluoropolymer electrolyte solution may contain one or more of emulsions, suspensions, colloidal liquids, and micellar liquids. An emulsion is a liquid in which liquid particles are dispersed as colloidal particles or larger particles to form a milky liquid. A suspension is a liquid in which solid particles are dispersed as colloidal particles or particles that can be seen with a microscope. A colloidal liquid is a liquid in which macromolecules are dispersed, and a micellar liquid is a lyophilic colloidal dispersion system in which many small molecules are associated with each other through intermolecular forces.
[0058] In addition, the fluoropolymer electrolyte solution may be concentrated or filtered depending on the forming method and application of the electrolyte membrane. The concentration method is not particularly limited, but examples include a method of heating the fluoropolymer electrolyte solution to evaporate the solvent and a method of concentrating under reduced pressure. When the fluoropolymer electrolyte solution is used as a coating solution, the solid content of the fluoropolymer electrolyte solution is preferably 0.5% by mass or more and 50% by mass or less from the viewpoint of suppressing an increase in viscosity to improve handleability and improving productivity. By making it 0.5% by mass or more, the viscosity required for coating can be ensured, and by making it 50% by mass or less, the viscosity can be made coatable.
[0059] The method of filtering the fluorine-based polymer electrolyte solution is not particularly limited, but a representative example is a method of filtering the solution under pressure using a filter. The filter preferably uses a filter medium having a 90% collection particle size of 10 to 100 times the average particle size of the solid particles contained in the fluorine-based polymer electrolyte solution. Examples of the material of the filter medium include paper and metal. In particular, when the filter medium is paper, the 90% collection particle size is preferably 10 to 50 times the average particle size of the solid particles. When a metal filter is used, the 90% collection particle size is preferably 50 to 100 times the average particle size of the solid particles. Setting the 90% collection particle size to 10 times or more of the average particle size is effective in suppressing the pressure required for sending the liquid from becoming too high and suppressing the filter from being clogged in a short period of time. On the other hand, setting the 90% collection particle size to 100 times or less of the average particle size is preferable from the viewpoint of being able to satisfactorily remove particle aggregates and undissolved resin that may cause foreign matter in the film.
[0060] The method for compounding the particulate reinforcing material with the fluoropolymer electrolyte membrane is not particularly limited, but for example, the reinforcing material is added to a fluoropolymer electrolyte solution in advance and then coated. More specifically, for example, a film of the fluoropolymer electrolyte solution to which the additive has been added is formed on a moving or stationary elongated casting substrate (sheet). This is then dried in a hot air circulating bath or the like to produce a composite electrolyte membrane.
[0061] The method of compounding the nanofiber sheet with the fluorine-based polymer electrolyte is not particularly limited, but may be, for example, a method of coating the nanofiber sheet with a fluorine-based polymer electrolyte membrane, or impregnating the nanofiber sheet with a fluorine-based polymer electrolyte solution, and then drying the nanofiber sheet. More specifically, for example, a film of the fluorine-based polymer electrolyte solution is formed on a moving or stationary elongated casting substrate (sheet), and the nanofiber sheet is brought into contact with the solution to produce an incomplete composite structure. This incomplete composite structure is dried in a hot air circulation tank or the like. Next, a film of the fluorine-based polymer electrolyte solution is further formed on the dried incomplete composite structure, thereby producing a composite electrolyte membrane. The contact between the fluorine-based polymer electrolyte solution and the nanofiber sheet may be performed in a dry state, a non-dried state, or a wet state.
[0062] The method for combining the reinforcing material having the form of a nonwoven fabric with the fluoropolymer electrolyte membrane can be the same as that for the nanofiber sheet.
[0063] The polymer electrolyte membrane of the present embodiment is preferably subjected to a heat treatment (also called annealing treatment) after being produced as described above. This heat treatment promotes crystallization of the perfluoroalkyl skeleton of the fluorine-based polymer electrolyte, and as a result, the mechanical strength of the electrolyte membrane can be further stabilized. The temperature of this heat treatment is preferably 100°C or higher and 230°C or lower, more preferably 120°C or higher and 220°C or lower, and even more preferably 140°C or higher and 210°C or lower. By setting the temperature at 100°C or higher, crystallization progresses and the membrane can be secured as a self-supporting membrane, by setting the temperature at 120°C or higher, the membrane can be provided with a strength that allows easy peeling from the substrate, and by setting the temperature at 140°C or higher, the mechanical strength of the electrolyte membrane can be improved. In addition, by setting the temperature at 230°C or lower, the decomposition of the polymer electrolyte can be suppressed, by setting the temperature at 220°C or lower, the generation of bubbles due to the volatilization of the solvent can be suppressed, and by setting the temperature at 210°C or lower, the water content of the electrolyte membrane can be appropriately maintained. The time of the heat treatment depends on the temperature of the heat treatment, but from the viewpoint of obtaining an electrolyte membrane having higher durability, it is preferably 1 minute to 3 hours, more preferably 5 minutes to 3 hours, and even more preferably 10 minutes to 2 hours. By setting it to 1 minute or more, the effect of the annealing treatment can be sufficiently ensured, by setting it to 5 minutes or more, the crystallization of the polymer electrolyte can be promoted, and by setting it to 10 minutes or more, a polymer electrolyte membrane having excellent mechanical strength can be obtained. In addition, by setting it to 3 hours or less, the deterioration of the polymer electrolyte membrane due to heating can be prevented, and by setting it to 2 hours or less, the water content of the electrolyte membrane can be maintained. For example, when the temperature of the heat treatment is 140°C or more and 210°C or less, it is particularly preferable to set it to 1 minute to 30 minutes. By setting it to 1 minute or more, the effect of the annealing treatment can be sufficiently ensured, and by setting it to 30 minutes or less, the decomposition of the reinforcing material can be suppressed.
[0064] The polymer electrolyte membrane of the present embodiment is particularly suitable for use as an electrolyte membrane in a solid polymer fuel cell. The polymer electrolyte membrane of the present embodiment has high durability against chemical deterioration of the electrolyte membrane components caused by peroxides and radicals without the addition of inorganic compounds, and since no inorganic compounds are added, it is possible to provide an electrolyte membrane for a fuel cell reinforced with a porous body that does not experience a decrease in power generation characteristics due to uneven distribution of additives inside the fuel cell during long-term operation. EXAMPLES
[0065] The present embodiment will be described in detail below with reference to examples, but the present invention is not limited to these examples. The evaluation and measurement methods used in the present embodiment are as follows.
[0066] [Example 1] A solution containing 15% by mass of perfluorocarbon sulfonic acid resin in water:ethanol = 40:60 (mass ratio) was prepared. This was designated solution 1. Solution 1 was applied to a stationary substrate film (Toray DuPont Co., Ltd., product name "Kapton 300H"; the same applies below) using a blade coater. Next, a PES fiber sheet (hereinafter referred to as "PES-NF"), which is a reinforcing material, was brought into contact with the solution 1 applied to the substrate film, impregnated, and then dried in a dryer (Espec Corp., model "SPH-201M") at 60°C for 20 minutes and at 120°C for 20 minutes. Solution 1 was applied to the dried film, and it was again dried in a dryer at 60°C for 20 minutes and at 120°C for 20 minutes. The electrolyte membrane thus obtained was annealed for 5 minutes with hot air at 170°C to obtain a polymer electrolyte membrane as a composite electrolyte membrane having a thickness of 15 μm. The obtained polymer electrolyte membrane was immersed in ethanol to extract decomposition products, and the structure of the ionic compound containing sulfur atoms was identified by IC-MS, and the compounds [IV], [V], and [VI] generated simultaneously were quantitatively analyzed by GC / MS to determine the content of the decomposition products contained in the polymer electrolyte membrane as the number of parts by mass per part by mass of the polymer electrolyte membrane. The content of the decomposition products was taken as the content of the ionic compound containing sulfur atoms. The quantitative analysis by GC / MS was performed by the following method. The decomposition product, diphenyl ether (DPE), was extracted into ethanol, and the total ion chromatogram (TIC) was obtained according to the following <GC / MS measurement conditions>. The solution concentration was determined from the peak area value of the TIC, and the concentration of the test sample was calculated by calculation. The calibration curve for calculating the solution concentration from the peak area value was prepared using the results of the TIC of the standard sample (DPE).
[0067] <GC / MS measurement conditions> Apparatus: Agilent 7890 / MSD5975C Column: DB-1 (0.25 mm i.d. × 30 m), liquid phase thickness 0.25 μm Column temperature: After maintaining at 40 °C for 5 minutes, the temperature was increased at 20 °C / min and maintained at 300 °C for 12 minutes. Column flow rate: 1.0 mL / min Inlet temperature: 300 °C Injection method: Split method (split ratio: 1 / 10) Ion source temperature: 230 °C Interface temperature: 300 °C Ionization method: Electron ionization (EI) method Sample volume: 1 μL injection
[0068] [Example 2] The same method as in Example 1 was carried out up to the step of drying again at 120 °C for 20 minutes. The annealing method was an infrared heating method. Specifically, annealing was performed for 1 minute by heating with infrared rays so that the surface temperature of the electrolyte membrane reached 170 °C, and a composite electrolyte membrane with a thickness of 15 μm was obtained. The content of the ionic compound containing sulfur atoms was determined in the same manner as in Example 1.
[0069] [Example 3] A composite electrolyte membrane with a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions described in Example 3 of Table 1 were used, that is, the annealing time was changed to 1 minute. The content of the ionic compound containing sulfur atoms was determined in the same manner as in Example 1.
[0070] [Example 4] A composite electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions were as shown in Example 4 in Table 1, that is, the annealing time was changed to 15 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1.
[0071] [Example 5] A composite electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions were as shown in Example 5 in Table 1, that is, the annealing time was changed to 25 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1.
[0072] [Example 6] A composite electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions in Example 6 in Table 1 were used, that is, PSU was used as the reinforcing material, the annealing temperature was set to 150° C., and the annealing time was changed to 10 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1.
[0073] [Example 7] A composite electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions in Example 7 in Table 1 were used, that is, PPS particles were used as the reinforcing material, and the annealing time was changed to 20 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1, except that the decomposition product to be quantified was changed to benzene.
[0074] [Example 8] A composite electrolyte membrane having a thickness of 20 μm was obtained in the same manner as in Example 1, except that the conditions were as shown in Example 8 in Table 1, that is, a PES nonwoven fabric was used as the reinforcing material and the annealing time was changed to 10 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1.
[0075] [Comparative Example 1] A composite electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions were as shown in Comparative Example 1 in Table 1, that is, the annealing time was changed to 0.5 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1.
[0076] [Comparative Example 2] A composite electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions were changed to those in Comparative Example 2 in Table 1, that is, the annealing temperature was changed to 160° C. and the annealing time was changed to 60 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1.
[0077] [Comparative Example 3] A composite electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Example 1, except that the conditions were as shown in Comparative Example 3 in Table 1, that is, the annealing time was changed to 30 minutes. The content of the ionic compound containing a sulfur atom was determined in the same manner as in Example 1.
[0078] [Comparative Example 4] A solution prepared so that the content of phenothiazine (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) in solution 1 was 110.0 ppm was used as solution 2, which was applied to the substrate film that had been left stationary using a blade coater. The solution was dried in a dryer at 60°C for 20 minutes and at 120°C for 20 minutes. The electrolyte membrane thus obtained was annealed with hot air at 170°C for 5 minutes to obtain a polymer electrolyte membrane having a thickness of 15 μm.
[0079] [Comparative Example 5] A polymer electrolyte membrane having a thickness of 15 μm was obtained in the same manner as in Comparative Example 4, except that the conditions were changed to those shown in Comparative Example 5 in Table 2, that is, the content of phenothiazine was changed to 192 ppm.
[0080] <Fuel cell evaluation> In order to investigate the initial cell characteristics (hereinafter referred to as "initial characteristics") of the membrane / electrode assembly produced below, the following fuel cell evaluation was carried out. To 1.00 g of Pt-supported carbon (TEC10E40E manufactured by Tanaka Kikinzoku Kogyo K.K., Japan, with 36.4 mass% Pt), 7.33 g of a polymer electrolyte solution was added, and then it was thoroughly mixed with a homogenizer to obtain an electrode catalyst composition. This electrode catalyst composition was applied onto a polytetrafluoroethylene (PTFE) sheet by the screen printing method. After application, it was dried at room temperature for 1 hour and then at 160 °C in air for 1 hour. In this way, an electrode catalyst layer with a size of 3.5 cm square and a thickness of 10 μm was obtained. Among these electrode catalyst layers, the one with a Pt loading of 0.15 mg / cm 2 was used as the anode catalyst layer, and the one with a Pt loading of 0.30 mg / cm 2 was used as the cathode catalyst layer. The anode catalyst layer, the cathode catalyst layer, and the polymer electrolyte membrane to be prepared below were provided facing each other at the center, sandwiched between them, and hot-pressed at 180 °C and a surface pressure of 0.1 MPa to transfer and bond the anode catalyst layer and the cathode catalyst layer to the polymer electrolyte to prepare a MEA.
[0081] <I-V Test> Next, the anode-side gas diffusion layer and the cathode-side gas diffusion layer were faced each other, the MEA was sandwiched, and incorporated into an evaluation cell. As the gas diffusion layer, carbon cloth (ELAT (registered trademark) B-1 manufactured by De Nora North America, USA) was set and incorporated into the evaluation cell. This evaluation cell was set in an evaluation apparatus (manufactured by Chino Corporation, Japan), heated to 80 °C, then hydrogen gas was flowed at 300 cc / min on the anode side and air gas at 800 cc / min on the cathode side, and both the anode and the cathode were pressurized at 0.15 MPa (absolute pressure). The water bubbling method was used for gas humidification, and the hydrogen gas was humidified at 85 °C and the air gas at 75 °C and supplied to the cell, and the current-voltage curve was measured to examine the initial characteristics.
[0082] <OCV Accelerated Test> In order to accelerate the evaluation of the oxidation resistance of the polymer electrolyte membrane under high temperature and low humidity conditions, the following OCV accelerated test was carried out. Here, "OCV" stands for open circuit voltage. This OCV accelerated test is an accelerated test intended to promote chemical deterioration of the polymer electrolyte membrane by maintaining it in an OCV state. For the OCV accelerated test, please refer to the method described in detail on pages 53-57 of the report on the results of the 2002 New Energy and Industrial Technology Development Organization (NEDO) commissioned research project "Research and development of polymer electrolyte fuel cells (establishment of accelerated membrane evaluation technology, etc.)" by Asahi Kasei Corporation, Japan. Specifically, first, the anode gas diffusion electrode and the cathode gas diffusion electrode were placed opposite each other, a polymer electrolyte membrane was sandwiched between them, and the resulting mixture was assembled into an evaluation cell. The gas diffusion electrode was a gas diffusion electrode ELAT (registered trademark) (Pt loading: 0.4 mg / cm) manufactured by DENORA NORTH AMERICA, USA. 2 (hereinafter the same) was coated with a 5% by mass solution of perfluorosulfonic acid polymer (Aciplex-SS (Asahi Kasei Corporation, equivalent weight (EW): 910, solvent composition (mass ratio): ethanol / water = 50 / 50) and then dried and fixed at 140 °C in an air atmosphere. The polymer loading amount was 0.8 mg / cm. 2 This evaluation cell was set in an evaluation device (manufactured by Chino Corporation, Japan) and heated, after which hydrogen gas was flowed to the anode side and air gas to the cathode side at 200cc / min to maintain an OCV state. A water bubbling method was used for gas humidification, and both hydrogen gas and air gas were humidified and supplied to the cell. The test conditions were a cell temperature of 100°C, a gas humidification temperature of 50°C, and no pressure (atmospheric pressure) on both the anode and cathode sides. Every 10 hours from the start of the test, hydrogen gas permeability was measured using a flow-type gas permeability measuring device GTR-100FA manufactured by GTR Tech Co., Ltd., Japan, to check whether pinholes had occurred in the polymer electrolyte membrane. With the anode side of the evaluation cell held at 0.15 MPa with hydrogen gas, argon gas was flowed as a carrier gas at 10 cc / min to the cathode side, and the hydrogen gas that had permeated from the anode side to the cathode side due to cross leakage through the evaluation cell was introduced into a gas chromatograph G2800 to quantify the amount of hydrogen gas permeation. The hydrogen gas permeation amount was expressed as X (cc), the correction coefficient as B (=1.100), the thickness of the polymer electrolyte membrane as T (cm), the hydrogen partial pressure as P (Pa), and the hydrogen permeation area of the polymer electrolyte membrane as A (cm 2 ), hydrogen gas permeability L (cc×cm / cm 2 / sec / Pa) was calculated using the following formula: L = (X × B × T) / (P × A × D) When the hydrogen gas permeability reached 10 times the value before the OCV test, it was determined that a cross leak had occurred and the test was terminated.
[0083] [Table 1]
[0084] The OCV accelerated test (chemical durability) was evaluated as a relative value, with the time until the OCV value in Example 1 fell below 720 mV being set as 1. When the OCV value was 1.5 times or more the time until the OCV value fell below 720 mV in Example 1, it was evaluated as ⊚, when it was 1 to less than 1.5 times, it was evaluated as ◯, and when it was less than 1 time, it was evaluated as x. The IV (power generation characteristics) was evaluated at a current density of 1.0 A / cm 2 When the cell voltage at the time of the test was reduced by less than 10 mV compared to a battery without catalyst poisoning, it was marked as ◯; when it was reduced by 10 mV or more but less than 20 mV, it was marked as △; when it was reduced by 20 mV or more, it was marked as ×.
[0085] [Table 2]
[0086] Table 1 compares the amount of ionic compound containing sulfur atoms and the effect of improving OCV chemical durability. Examples 1 to 8 show that polymer electrolyte membranes containing ionic compound containing sulfur atoms in an amount of 0.5 to 93 ppm have excellent OCV chemical durability. On the other hand, Comparative Example 1 shows that the effect of improving OCV chemical durability is not achieved when the content of ionic compound containing sulfur atoms is less than 0.10 ppm.
[0087] Table 1 compares the amount of ionic compound containing sulfur atoms and the degradation of IV power generation characteristics. From Examples 1 to 3, 5 to 8 and Comparative Example 1, it can be seen that the polymer electrolyte membranes having an ionic compound containing sulfur atoms of 0.06 to 20 ppm show almost no degradation in IV power generation characteristics. On the other hand, from Examples 4 and 5, it can be seen that the polymer electrolyte membranes having an ionic compound containing sulfur atoms of 42 to 93 ppm show a slight degradation in IV power generation characteristics. Furthermore, from Comparative Examples 2 and 3, it is considered that when the content of ionic compound containing sulfur atoms exceeds 100 ppm, the IV power generation characteristics are significantly degraded.
[0088] To summarize these results, it can be said that a polymer electrolyte membrane having an ionic compound content containing a sulfur atom of 0.10 to 100 ppm has excellent OCV chemical durability without causing any substantial decrease in IV power generation characteristics.
[0089] Table 2 compares whether the compound containing a sulfur atom is an ionic compound or a heterocyclic compound. The results of Example 2 show that when the amount of the compound containing a sulfur atom is 5 ppm, the OCV chemical durability is excellent and there is almost no deterioration in the IV power generation characteristics. On the other hand, Comparative Examples 4 and 5 show that when the compound containing a sulfur atom is a heterocyclic compound, the same OCV chemical durability as that of an ionic compound cannot be achieved unless 110 ppm or more of the sulfur component is added, and the IV power generation characteristics deteriorate due to the large amount of sulfur component added.
[0090] From this, it can be seen that compounds containing sulfur atoms in the polymer electrolyte membrane that have ionic properties can exhibit the effect of improving OCV chemical durability in small amounts. In addition, because there are fewer compounds containing sulfur atoms, it can be seen that the IV power generation characteristics are not deteriorated. This is thought to be because compounds that have ionic properties can be stably dispersed and exist in the water generated by power generation inside the fuel cell, so that the effect can be exhibited even with a small amount added. [Industrial Applicability]
[0091] The polymer electrolyte membrane of the present invention has excellent chemical durability while maintaining power generation properties. [Explanation of symbols]
[0092] 1... Reinforcement composite layer, 2, 4: Electrolyte polymer layer, 3. Particulate Reinforcement Materials
Claims
1. A polymer electrolyte, A reinforcing material having one or more forms selected from particles, a fiber sheet, and a nonwoven fabric; an ionic compound containing a sulfur atom; A polymer electrolyte membrane comprising: The reinforcing material includes at least one polymer selected from polyethersulfone, polyphenylene sulfide, and polysulfone; the content of the ionic compound containing a sulfur atom is 0.10 ppm or more and 7.3 ppm or less, expressed as parts by mass per part by mass of the polymer electrolyte membrane; A polymer electrolyte membrane, wherein the proportion of the reinforcing material is 1 to 20 mass % based on the total amount of the polymer electrolyte membrane.
2. The molecular weight of the ionic compound containing a sulfur atom is 300 g / mol or less. The polymer electrolyte membrane according to claim 1 .
3. The sulfur atom-containing ionic compound is represented by formula (1): The polymer electrolyte membrane according to claim 1 or 2. 【Chemistry 1】 (In the formula, R represents a monovalent organic group having 1 to 10 carbon atoms, hydrogen, or a hydroxyl group.)
4. A solid polymer fuel cell comprising the polymer electrolyte membrane according to any one of claims 1 to 3.
Citation Information
Patent Citations
JP1973010868B1
JP1973095563A
JP1974072867A
Attack wow circuit of electronic musical instruments
JP1978031122A
Semiconductor storage device
JP1982098186A